Impact of Pseudomonas aeruginosa Isolation on Mortality and Outcomes in an Outpatient Chronic Obstructive Pulmonary Disease Cohort - Jacobs, David M (Open Forum Infect Dis, 2020)
BACKGROUND: Tracheobronchial colonization by Pseudomonas aeruginosa (PA) has been shown to negatively impact outcomes in cystic fibrosis and bronchiectasis. There is uncertainty whether the same association is prevalent in chronic obstructive pulmonary disease (COPD), especially in the outpatient setting. Our objective was to determine (1) whether PA isolation is associated with mortality and (2) changes in exacerbation and hospitalization rates within a longitudinal cohort of COPD outpatients. METHODS: Pseudomonas aeruginosa colonization was ascertained in monthly sputum cultures in a prospective cohort of COPD patients from 1994 to 2014. All-cause mortality was compared between patients who were colonized during their follow-up period (PA(+)) and those who remained free of colonization (PA(−)); Cox proportional hazards models were used. Exacerbation and hospitalization rates were evaluated by 2-rate χ (2) and segmented regression analysis for 12 months before and 24 months after PA isolation. RESULTS: Pseudomonas aeruginosa was isolated from sputum in 73 of 181 (40%) patients. Increased mortality was seen with PA isolation: 56 of 73 (77%) PA(+) patients died compared with 73 of 108 (68%) PA(−) patients (P = .004). In adjusted models, PA(+) patients had a 47% higher risk of mortality (adjusted hazard ratio = 1.47; 95% confidence interval, 1.03–2.11; P = .04). Exacerbation rates were higher for the PA(+) group during preisolation (15.4 vs 9.0 per 100 person-months, P < .001) and postisolation periods (15.7 vs 7.5, P < .001). Hospitalization rates were higher during the postisolation period among PA(+) patients (6.25 vs 2.44, P < .001). CONCLUSIONS: Tracheobronchial colonization by PA in COPD outpatients was associated with higher morbidity and mortality. This suggests that PA likely contributes to adverse clinical outcomes rather than just a marker of worsening disease.